The online classroom, a place where no virus can enter: UiTM Sarawak undergraduates' engagement during the COVID-19 pandemic / Caesar Delwis ... [et al.] - Delwis, Caesar; Sarkawi, Adib; Johari, Aiza; Chachil, Ketty; Morni, Affidah (Universiti Teknologi MARA Cawangan Sarawak, 2024)
COVID-19 has undeniably shifted the educational landscape in Malaysia and the overnight decision to switch to online teaching and learning has presented challenges for students in Sarawak, which is the largest state in Malaysia. After the COVID-19 movement control order was lifted and many undergraduates returned to campuses, they expressed their relief at no longer having to contend with the detrimental effects of online learning, such as heightened stress and anxiety, which led to a range of psychosocial issues. Despite some students gaining valuable experiences from these new learning environments, a significant number have faced challenges in maintaining motivation for their courses. The objective of this study is to investigate and examine the reasons affecting the online learning challenges faced by university students in Sarawak. The challenges impacting students' engagement in online learning were examined through the investigation of five independent variables namely, personality, behavioural, technological savviness, availability of home Internet access, and the structure of the online courses. A set of questionnaires, along with data from focus group interviews, were used to collect information from a total of 102 participants. These participants were selected from two branch campuses of a local university situated in Samarahan, Sarawak. The implication of this study to update knowledge with a wide range of student satisfaction and motivation through online learning during the COVID-19 pandemic, especially to improve student satisfaction and motivation for a successful learning process suggests that it can be considered an effective learning method. This study is beneficial for education experts, lecturers, teachers, trainers, and technologists who are interested in assessment, learning, guidance, design, and online-based learning environments during a pandemic or after a pandemic to increase motivation and satisfaction in learning.